1995
DOI: 10.1038/373216a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PLC-mediated signalling in vivo by CDP-diacylglycerol synthase

Abstract: CDP-diacylglycerol synthase (CDS) is an enzyme required for the regeneration of the signalling molecule phosphatidylinositol-4,5-bisphosphate (PtdlnsP2) from phosphatidic acid. A photo-receptor cell-specific isoform of CDS from Drosophila is a key regulator of phototransduction, a G-protein-coupled signalling cascade mediated by phospholipase C. cds mutants cannot sustain a light-activated current as a result of depletion of PtdlnsP2. Overexpression of CDS increases the amplitude of the light response, demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 48 publications
4
156
0
Order By: Relevance
“…These include the DAG kinase (RDGA), cytidine diphosphate (CDP)-DAG synthase (CDS) and the PI synthase (PIS), which catalyzes the production of phosphatidic acid (PA), CDP-DAG, and PI, respectively (Fig. 6a) [28,29,[131][132][133]. In addition, a PI transfer protein (RDGB) may function in the transfer of PIs from the SRC to the rhabdomeres [29,134,135].…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the DAG kinase (RDGA), cytidine diphosphate (CDP)-DAG synthase (CDS) and the PI synthase (PIS), which catalyzes the production of phosphatidic acid (PA), CDP-DAG, and PI, respectively (Fig. 6a) [28,29,[131][132][133]. In addition, a PI transfer protein (RDGB) may function in the transfer of PIs from the SRC to the rhabdomeres [29,134,135].…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
“…In addition, a PI transfer protein (RDGB) may function in the transfer of PIs from the SRC to the rhabdomeres [29,134,135]. If the levels of CDS or PIS are reduced but not eliminated, a light response can still be obtained if the flies are dark-adapting [131,132]. However, the flies are not able to sustain a light response.…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent immunolocalization studies by Lee et al (2003) have shown that light-dependant translocation of Arr2 to and from the rhabdomere is impaired in cds (Wu et al, 1995) and rdgB (Vihtelic et al, 1993(Vihtelic et al, ,1991 mutants, in which PI biogenesis and trafficking are disrupted, respectively. They, furthermore, showed that in PTEN; dAkt and PTEN overexpression (Huang et al, 1999;Stocker et al, 2002) mutants, in which metabolism of PIP 3 is defective, Arr2 translocation was also impaired.…”
Section: Light Adaptation Through Phosphoinositide and Ninac Myosin Imentioning
confidence: 99%
“…Two overlapping ESTs from Arabidopsis tkaliana, T45653 and N97146, were found with a "bait" amino acid sequence of CDS from Esckerickia coli. The ESTs contained a continuous open reading frame that encoded a partia1 protein with highest sequence homology to the CDS of Drosophila melanogaster (Wu et al, 1995) and Sacchnromyces cerevisiae (Shen et al, 1996). A 317-bp molecular probe was generated by PCR with forward primer 5'-GGCCTTTAATAAAGCTGTCTCC-3' and reverse primer 5'-TACCGAAAAACCCCCCAAAAGG-3' from 50 ng of first-strand cDNA, which was prepared from poly(A)+ RNA of rosette leaves of A. tkaliana ecotype C-24.…”
Section: Cloning and Sequencing Of Cdnasmentioning
confidence: 99%